Safety evaluation of concrete gravity dams sliding considering the variability of rock mass foundation hydraulic and mechanical properties - Pereira, R. (2015)
In many countries, including Portugal, the design of concrete dams is based on the use of a global safety factor. Adopting a probabilistic safety approach, the Eurocodes are based on the principles of the limit states design in conjunction with the partial safety factors method. Thus, to develop a compatible approach for the design of concrete dams, it is important to understand the contribution of the uncertainty of the hydraulic and mechanical rock mass properties to the safety of concrete gravity dams for the design loads, including high intensity seismic actions. In this work, a set of Portuguese gravity dams are assessed in a reliability framework, combining both design data and data collected in the service lifetime. Geometrical data, as well as the dead-weight action, the hydrostatic pressure and the maximum design earthquake were considered as deterministic variables. The coefficient of friction and the uplift , quantified by means of a factor under the drainage line, were considered as probabilistic variables. Using the Monte Carlo method, the frequency of violating the safety criteria under extreme seismic actions was evaluated for six dams. An annual probability of failure of 10-5 was obtained for a high intensity seismic occurrence, which is the value defined in t he national appendix of Eurocode 8 for a return period of 1000 years.